A Descriptive Study of Pragmatic Competence in Libyan EFL Academic Discourse (Comprehensive Journal of Science, 2026)
This descriptive study examines pragmatic competence in Libyan EFL academic discourse. Pragmatic competence refers to the ability to use language appropriately according to context, purpose, and social norms. Although Libyan university students often demonstrate adequate grammatical knowledge, many face difficulties when using English effectively in academic interactions. This study analyzes authentic academic discourse produced by Libyan EFL learners to describe their use of speech acts, politeness strategies, and context-sensitive language features. Using a descriptive qualitative approach, the study aims to identify common pragmatic patterns and challenges without implementing any instructional intervention. The findings are expected to contribute to a clearer understanding of pragmatic performance in the Libyan EFL context and to provide pedagogical insights for improving pragmatic awareness in university-level English programs.
Keywords: pragmatic competence, academic discourse, EFL learners, descriptive study, Libyan context